Post-stroke Cognitive Impairment—Impact of Follow-Up Time and Stroke Subtype on Severity and Cognitive Profile: The Nor-COAST Study - Aam, Stina; Einstad, Marte Stine; Munthe-Kaas, Ragnhild; Lydersen, Stian; Ihle-Hansen, Hege; Knapskog, Anne-Brita; Ellekjær, Hanne; Seljeseth, Yngve; Saltvedt, Ingvild (Frontiers in Neurology, 2020)
BACKGROUND: Post-stroke cognitive impairment (PSCI) is common, but evidence of cognitive symptom profiles, disease course over time, and pathogenesis is scarce. We investigated whether time and etiologic stroke subtype were of importance for the probability for PSCI and severity and cognitive profile. METHODS: Stroke survivors (n=617) underwent cognitive assessments of attention, executive function, memory, language, perceptual-motor function and administered the Montreal Cognitive Assessment (MoCA) after 3 and/or 18 months. PSCI was classified according to Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria. Stroke severity was assessed with the National Institutes of Health Stroke Scale (NIHSS) at admittance and stroke subtype was categorized as intracerebral hemorrhage (ICH), large artery disease (LAD), cardioembolic stroke (CE), small vessel disease (SVD), un-/other determined strokes (UD). Mixed-effects logistic or linear regression was applied, with PSCI, MoCA, and z-scores of the cognitive domains as dependent variables. Independent variables were time as well as stroke subtype, time, and interaction between these. The analyses were adjusted for age, education, and sex. RESULTS: Mean age was 72 years (SD 12), 42 % were females, and mean NIHSS score at admittance was 3.8 (SD 4.8). Probability for PSCI after 3 and 18 months was 0.59 (95%CI 0.51-0.66) and 0.51 (95%CI 0.52-0.60) respectively and did not change over time. Global measures and almost all cognitive domains were impaired for the entire stroke population and for almost all stroke subtypes. Executive function and language improved for the entire stroke population, and after dividing the sample according to stroke subtypes, language improved for ICH patients. No significant differences were found in the severity of impairment between stroke subtypes, except for attention which was impaired for LAD and CE in contrast to no impairment for SVD. CONCLUSIONS: PSCI is common for all stroke subtypes, with impairment in several cognitive domains noted early after a stroke as well as a long time after a stroke. Increased evidence of symptom profile might be important for personalizing rehabilitation, while stroke subtypes may offer new insight into underlying mechanisms. Further research is needed on underlying mechanisms, prevention and treatment of PSCI, and on relevance for rehabilitation.